(untitled) (London Journal of Research In Humanities and Social Sciences, 2025)
This essay examines the historical and theological evolution of Liberation Ecclesiology in Latin America. The objective is to provide critical reflections on the attacks that Liberation Ecclesiology has suffered over the past century. Initially, the Latin American Catholic Church was influenced by medieval essentialist theology, which opposed socialism. In the twentieth century, Liberation Theology emerged in response to the theoretical-theological crisis faced by "revolutionary Christians" engaged in political struggle. This theology proposed rethinking salvation in relation to the historical process of liberation. The critique of European theology by Latin American theologians introduced a historical character to soteriology, leading the Church to recognize the necessity of constructing the Kingdom of God among people through historical processes of liberation. Liberation Ecclesiology sought to renew ecclesial practices but faced opposition from traditional European theology. Political factors, such as U.S. influence and the rise of neoconservatism during Reagan’s administration, also impacted Liberation Theology. Despite criticisms, Liberation Theology remains active, adapting to new realities and diversifying into areas such as feminist, Indigenous, and African theology. The election of Pope Francis brought renewed hope to this theology, which strives to remain relevant in a globalized world.